Integrated Strategy From In Vitro, In Situ, In Vivo to In Silico for Predicting Active Constituents and Exploring Molecular Mechanisms of Tongfengding Capsule for Treating Gout by Inhibiting Inflammatory Responses - Yang, Wenning; Jiang, Xiaoquan; Liu, Jingtong; Qi, Dongying; Luo, Zhiqiang; Yu, Guohua; Li, Xueyan; Sen, Muli; Chen, Hongjiao; Liu, Wei; Liu, Yang; Wang, Guopeng (Frontiers in Pharmacology, 2021)
The study of screening active constituents from traditional Chinese medicine (TCM) is important for explicating the mechanism of action of TCM and further evaluating safety and effect effectively. However, detecting and identifying the active constituents from complicated biological samples still remain a challenge. Here, a practical, quickly and novel integrated strategy from in vitro, in situ, in vivo to in silico for rapidly screening the active constituents was developed. Firstly, the chemical profile of TCM in vitro was identified by using UPLC-Q Exactive-Orbitrap HRMS. Secondly, the in situ intestinal perfusion with venous sampling (IPVS) method was used to investigating intestinal absorption components. Thirdly, after intragastrical administration of TCM extract, the in vivo absorbed prototype components were detected and identified. Finally, the target network pharmacology approach was used to explore the potential targets and possible mechanisms of the absorbed components from TCM. The reliability and availability of this approach was demonstrated by using Tongfengding capsule (TFDC) as an example of herbal medicine. A total of 141 compounds were detected and identified in TFDC, and among them, 64 components were absorbed into the plasma. Then, a total of 35 absorbed bioactive components and 50 related targets shared commonly by compounds and gout were integrated via target network pharmacology analysis. These results demonstrated that this original method may provide a practical tool for screening bioactive compounds from TCM treating particular diseases. Furthermore, it also can clarify the potential mechanism of action of TCM.